Modelling of Catalytic Converter in CNGV Cold-start Engine - Jolius, Gimbun; Chuah, T.G; Thomas, S. Y. Choong; Sahari, Barkawi; Fakhru'l-Razi, A (Institute of Advanced Technology, 2004)
Modelling of cold-start engine behaviour at catalytic converter is a difficult task as it involves complicated convection-diffusion-reactions flow.This work presents a CFD calculation to predict the transient thermal and conversion characteristics of catalytic converter during the light-off operation for a different position of catalytic converter from engine. The effect of exhaust length on conversion of NOx to N2 and CO to CO2 are numerically evaluated via CFD. It shows that the light-off condition will take a longer time as the position of catalytic converter from engine is lengthened and it is proposed that the ideal position of catalytic converter from engine should no longer than 0.5 m.